Dimensions of Sexual Self-Concept in Women with Endometriosis: A Qualitative Exploration - Rostami, Mehdi; Saeidtaleshi, Leila (Journal of Personality and Psychosomatic Research (JPPR), 2025)
This study aimed to explore and interpret the dimensions of sexual self-concept among women living with endometriosis, focusing on how chronic pelvic pain, emotional distress, and relational factors shape their perceptions of sexuality and identity. A qualitative exploratory design was employed using semi-structured, in-depth interviews with 20 women diagnosed with endometriosis residing in Canada. Participants were selected through purposive sampling, ensuring variation in age, marital status, and duration since diagnosis. Interviews continued until theoretical saturation was achieved. Data were analyzed using thematic analysis following Braun and Clarke’s six-phase framework, supported by NVivo 14 software for coding and data organization. Trustworthiness was ensured through member checking, peer debriefing, and maintaining an audit trail. Analysis revealed three overarching themes: (1) Altered Body and Self-Perception, describing loss of femininity, body shame, and internalized guilt; (2) Emotional and Relational Challenges in Sexual Intimacy, highlighting fear of pain, avoidance of intercourse, communication barriers, and relational insecurity; and (3) Coping, Adaptation, and Sexual Empowerment, encompassing self-acceptance, meaning-making, spiritual coping, and redefinition of sexual identity. Participants demonstrated both vulnerability and resilience, reconstructing their sexual self-concept through self-compassion, supportive relationships, and advocacy. The findings indicate that endometriosis affects not only physical sexuality but also emotional identity and relational dynamics. Sexual self-concept in women with endometriosis is a multidimensional construct shaped by pain, body image, partner understanding, and personal meaning-making. The study underscores the importance of integrating psychosocial and relational support into endometriosis care to promote sexual well-being and identity reconstruction.